Overcoming your alcohol or drug problem : effective recovery strategies : workbook - Daley, Dennis C. (Treatments that work., 2006)
This workbook, reviews issues in the assessment and treatment of all types of substance use disorders. The guide provides clinicians with strategies for working with substance use disorders by focusing on specific issues involved in both stopping substance use and changing behaviors or lifestyle aspects that contribute to continued substance abuse.